Indonesian oil exports and imports and its membership status in OPEC - Abdurofiq, Atep; Putra, Gilang Rizki Aji; Yunus, Nur Rohim (BULETIN ADALAH, 2024)
Indonesia is a significant producer and exporter of oil, a commodity that plays a vital role in the economy of the entire world. Within the scope of this study, the dynamics of Indonesia's oil exports and imports, as well as its membership status in OPEC, are investigated. To have a better understanding of the influence that Indonesia's membership in OPEC has had on the country's economy and the role that Indonesia plays in the global oil market, a detailed examination of Indonesia's oil trade data is utilised. The findings of this study have the potential to offer significant insights that Indonesia can use in its economic strategy and its connection with international oil organisations.